Assessment of early and late dry age-related macular degeneration with spectral-domain optical coherence tomography and fundus autofluorescence - Singh, Archana; Agrawal, Mohini; Vannadil, Harikrishnan; Bhatta, Sunandan (Indonesian Vitreoretinal Society, 2024)
Aim: To assess features of early and late dry age-related macular degeneration (ARMD) using spectral-domain optical coherence tomography (SDOCT) versus fundus Autofluorescence (FAF). Method: Observational cross-sectional study conducted from January-2022 to December-2022 in a tertiary eye care center, India. Patients >55 years and clinically diagnosed dry ARMD underwent SDOCT and FAF. OCT and FAF were assessed and correlated with best-corrected visual acuity (BCVA). Results: 106 eyes of 60 cases were included. Mean age was 65.24+4.80 years. Mean BCVA was 0.4±0.24 LogMAR. Among clinically evident drusen, hard drusen (>63µm) was 88.6% (n=94 eyes), confluent soft-drusen 9% (n=10 eyes) and pigmentary changes at macula in 01 eye only. On OCT, 65% (n=69) eyes showed RPE irregularity, which was there in all the cases with soft drusen, whereas it varied in cases with hard drusen. On FAF, hypo/hyper was observed in 81 eyes (76%). When correlated with BCVA, RPE irregularity was not seen in cases with BCVA>6/12. An abnormality in macular autofluorescence was evident in 62% (n= 31) in cases with vision >6/12; whereas in cases with vision<6/18, it was seen in 80% (n=49) cases. A strong correlation was found between the OCT findings and abnormal FAF (kappa=0.60), suggesting comparable results by both the modalities in cases of early and late dry ARMD. Conclusion: OCT and FAF show good correlation in assessing early and late dry ARMD, thereby explaining the correlation between anatomical and biochemical changes. Thus, these can be used as a progression predictor, when used together.